COVID-19 and healthcare workers: A systematic review and meta-analysis - Gholami, Mandana (Int J Infect Dis, 2021)
BACKGROUND: The COVID-19 pandemic has focused attention on the challenges and risks faced by frontline healthcare workers (HCW). This study aimed to describe the clinical outcomes and risk factors for SARS-CoV-2 infection in HCW. METHODS: Three databases were surveyed and 328 articles were identified. Of these, 225 articles did not meet inclusion criteria; therefore, 97 full-text article were reviewed. Finally, after further revision, 30 articles were included in the systematic review and 28 were used for meta-analysis. RESULTS: Twenty-eight studies were identified involving 119,883 patients. The mean age of the patients was 38.37 years (95% CI 36.72–40.03) and males comprised 21.4% (95% CI 12.4–34.2) of the population of HCW. The percentage of HCW who tested positive for COVID-19 was 51.7% (95% CI 34.7–68.2). The total prevalence of comorbidities in seven studies was 18.4% (95% CI 15.5–21.7). The most prevalent symptoms were fever 27.5% (95% CI 17.6–40.3) and cough 26.1% (95% CI 18.1–36). The prevalence of hospitalisation was 15.1% (95% CI 5.6–35) in 13 studies and of death was 1.5% (95% CI 0.5–3.9) in 12 studies. Comparisons of HCW with and without infection showed an increased relative risk for COVID-19 related to personal protective equipment, workplace setting, profession, exposure, contacts, and testing. CONCLUSION: A significant number of HCW were reported to be infected with COVID-19 during the first 6 months of the COVID-19 pandemic, with a prevalence of hospitalisation of 15.1% and mortality of 1.5%. Further data are needed to track the continued risks in HCW as the pandemic evolves and health systems adapt.